Perlindungan Hukum Terhadap Hak Kekayaan Intelektual Kain Tenun di Kabupaten Nagekeo Ditinjau dari Undang-Undang Nomor 20 Tahun 2016 Tentang Merek dan Indikasi Geografis - Zenobius Dhegha Dhae; Sukardan Aloysius; Yossie Maria Y. Jacob (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this research is to analyze the legal protection of intellectual property rights of woven fabrics in Nagekeo Regency in terms of Law Number 20 of 2016 concerning trademarks and geographical indications. This type of research is Empirical Legal research, the type of data used in this research is qualitative descriptive data. The data used in the study based on the relevance of the source data, namely primary and secondary data. The results of this study suggest that: (1) The legal protection of the Weaving Craftsmen Group through the Nagekeo Weaving Geographical Indication Protection Society is that the community must immediately register the Nagekeo Ikat Weaving to the Ministry of Law and Human Rights to obtain legal protection, the protection of the Nagekeo Ikat Weaving uses law number 20 of 2016 concerning Trademarks and Geographical Indications. (2) the obstacles are low human resources, the complexity of the registration process, the lack of registration facilities that make the level of awareness of the importance of legal protection of woven fabrics will decrease. The people of Nagekeo Regency expect that this regional superior product of Tenun Ikat Nagekeo will receive legal protection from unauthorized use or counterfeiting of Tenun Ikat Nagekeo in the form of Geographical Indications.